2021
DOI: 10.1136/neurintsurg-2020-016732
|View full text |Cite
|
Sign up to set email alerts
|

Monitored anesthesia care during mechanical thrombectomy for stroke: need for data-driven and individualized decisions

Abstract: BackgroundThe optimal anesthesia management for patients with stroke undergoing mechanical thrombectomy (MT) during the COVID-19 pandemic has become a matter of controversy. Some recent guidelines have favored general anesthesia (GA) in patients perceived as high risk for intraprocedural conversion from sedation to GA, including those with dominant hemispheric occlusions/aphasia or baseline National Institutes of Health Stroke Scale (NIHSS) score >15. We aim to identify the rate and predictors of conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
2
1
Order By: Relevance
“…In our study, 11 out of 173 patients (6.4%) converted to GA of whom three patients (1.7%) were secondary to agitation or patient movement. This rate is comparable to a previously reported rate of 1.6%, with patient agitation being the most common reason 16. Several factors could cause patient movement and poor cooperation, for instance discomfort at the puncture site, a hot sensation due to injection of contrast material into the cerebral arteries and the pain associated with the traction of the blood vessels during catheter navigation, balloon inflation or stent deployment.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, 11 out of 173 patients (6.4%) converted to GA of whom three patients (1.7%) were secondary to agitation or patient movement. This rate is comparable to a previously reported rate of 1.6%, with patient agitation being the most common reason 16. Several factors could cause patient movement and poor cooperation, for instance discomfort at the puncture site, a hot sensation due to injection of contrast material into the cerebral arteries and the pain associated with the traction of the blood vessels during catheter navigation, balloon inflation or stent deployment.…”
Section: Discussionsupporting
confidence: 80%
“…Liebeskind et al [30] identi ed that the presence of HMCAS was associated with thrombi primarily composed of red blood cells (RBCs) in their study on thrombus composition analysis in patients undergoing MT for acute MCA occlusion. Recent research has indicated that RBC-dominant thrombi are associated with shorter procedure times during MT [31,32]. In contrast, our study identi ed that HMCAS is linked to an increased number of thrombectomy passes.…”
Section: Discussioncontrasting
confidence: 74%
“…As with any MAC case, conversion to general anesthesia with an invasive airway device is a possibility, and so proper preparation and resources must be in place for such an event. The rate of conversion from MAC to general anesthesia is relatively low, and no significant predictive factors have been reported [17]. There are, however, worse functional outcomes in those converted to general anesthesia compared with those remaining with MAC [18].…”
Section: Key Pointsmentioning
confidence: 98%